Influence of the proportion of particulate autogenous bone graft/platelet-rich plasma on bone healing in critical-size defects: An immunohistochemical analysis in rat calvaria - Nagata, Maria [UNESP]; Messora, Michel [UNESP]; Okamoto, Roberta [UNESP]; Campos, Natalia [UNESP]; Pola, Natalia [UNESP]; Esper, Luis [UNESP]; Sbrana, Michyele [UNESP]; Fucini, Stephen [UNESP]; Garcia, Valdir [UNESP]; Bosco, Alvaro [UNESP] (Elsevier B.V., 2009)
This immunohistochemical analysis evaluated the influence of the proportion of particulate autogenous bone (AB) graft/platelet-rich plasma (PRP) on bone healing in surgically created critical-size defects (CSD) in rat calvaria. 25 rats were divided into 5 groups: C (control), AB, AB/PRP-50, AB/PRP-100 and AB/PRP-150. A 5 mm diameter critical-size defect was created in the calvarium of each animal. In Group C, defect was filled by blood clot only. In Group AB, defect was filled with AB graft. In Groups AB/PRP-50, AB/PRP-100 and AB/PRP-150, defects were filled with AB graft combined with 50, 100 and 150 mu l of PRP, respectively. Animals were euthanized at 30 days post-operative. Osteocalcin (OC) and osteopontin (OP) immunohistochemical staining were performed. OP-positive and OC-positive cells were quantified. The amount of vital bone (VBA) and remaining bone graft particles (RPA) were calculated as percentage of the total area of the original defect. Data were statistically analyzed (ANOVA, Tukey, p<0.05).Group AB/PRP-100 presented a significantly higher number of OP-positive cells than groups C, AB/PRP-50 and AB/PRP-150 (p<0.05) and also a significantly higher number of OC-positive cells than all of the other groups (p<0.05). The number of OP-positive cells in Group AB/PRP-150 was significantly lower than in Group AB (p<0.05). Statistically significant differences were not found between groups with regard to either VBA or RPA (p>0.05). However, clear trends were indicated by an increase in VBA in Group AB/PRP-100 when compared to groups C. AB and AB/PRP-150 and an increase in RPA in Group AB/PRP-150 when compared to groups AB, AB/PRP-50 and AB/PRP-100.The proportion AB graft/PRP seems to influence bone healing in CSD in rat calvaria. The highest expression of osteocalcin and osteopontin, and thus the most developed healing, was found in Group AB/PRP-100 indicating that there may be an optimal proportion beyond which increasing the concentration PRP is deleterious. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bone regeneration; Growth factors; Platelets; Immunohistochemistry; Osteoblasts